2013
DOI: 10.18553/jmcp.2013.19.s1.s16
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Methods for Evaluating the Effectiveness of Intramuscular Interferon Beta-1a for Relapsing-Remitting Multiple Sclerosis

Abstract: Newer outcome-based assessment methods have been developed that complement and improve upon the ability of historical clinical and magnetic resonance imaging (MRI) outcome measures to measure multiple sclerosis (MS) disease activity, patient functionality, treatment efficacy, and the risk of MS disease progression. These newer MS outcome assessments include instruments to evaluate cognitive function and patient quality of life; enhanced measures of disability, such as the Multiple Sclerosis Functional Composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(78 reference statements)
0
1
0
1
Order By: Relevance
“…The magnitude of improvement as rated by the patients (between 7.7 and 14.3 points on a 25-point VAS) would appear clinically meaningful, but the relevance of the observed changes for patients cannot be currently assessed. In accordance with the AXIOM trial, the majority of trials with IM IFNb-1a showed a trend towards better quality of life, particularly in the physical domains, or at least a stable quality of life [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 70%
“…The magnitude of improvement as rated by the patients (between 7.7 and 14.3 points on a 25-point VAS) would appear clinically meaningful, but the relevance of the observed changes for patients cannot be currently assessed. In accordance with the AXIOM trial, the majority of trials with IM IFNb-1a showed a trend towards better quality of life, particularly in the physical domains, or at least a stable quality of life [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 70%
“…neuen oder sich vergrö-ßernden T2-Läsionen im MRT (Arnold et al 2014;Nixon et al 2014). Es wird zunehmend diskutiert, ob diese Parameter zur adäquaten Erfassung von Verlauf und Therapieerfolg ausreichend sind (Foley et al 2013), denn häufig sind mit einer MS auch neuropsychologische Symptome wie Fatigue und Depression assoziiert (7 Kap. 1).…”
Section: Radiologisch Isoliertes Syndromunclassified